Recent Social Trends - Bigelow, Karl W. (Quarterly Journal of Economics, 1933)
Journal Article Recent Social Trends Get access Karl W. Bigelow Karl W. Bigelow University of Buffalo Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 48, Issue 1, November 1933, Pages 150–170, https://doi.org/10.2307/1884800 Published: 01 November 1933